(untitled) (e-Journal of Linguistics, 2019)
Various languages in the world have their own systems, especially in terms of verb classification. It can determine argument in the structure. This paper is intended to analyze the interaction between syntax and semantics in terms of the argument structure of the slide verb in English. The main theory used in this study was the theory of argument structure proposed by Kim & Sells (2008). The result of analysis showed that two kinds of slide verb: bounce and slide are intransitive and transitive verbs. The specifier (SPR) of the sentence structure functions as the agent; the Complement (COMPS) of the verb bounce serves as the patient and the COMPS of the verb slide functions as the theme.